Proceedings of the 2017 5th International Conference on Mechatronics, Materials, Chemistry and Computer Engineering (ICMMCCE 20 2017
DOI: 10.2991/icmmcce-17.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on morphology and structure of Cu-Cr-Al2O3 powders prepared by mechanical milling

Abstract: Abastract:In this study, the effect of the milling time on microstructure of Cu-0.5 wt.% Cr-1 wt.% Al 2 O 3 was investigated. The lattice parameter was evaluated by the X-ray diffraction technique. The microstructure was characterized by scanning electron microscopy. Also, size and distribution of Cr and Al 2 O 3 were investigated by using X-rays energy dispersive (EDX) mapping. The result shows that the lattice parameter of the Cu phase increases with increasing milling time. The changing trend of Cu particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…however, a portion of the ceramic particles retained their shapes and were not alloyed. This indicated that sintering of the green compact, produced after pressing the mixed powder, may create voids owing to the ceramic particles that were deformed or retained their shape, resulting in the formation of pores in the composite [10][11][12][13]. The uniform distribution of additives in the Cu base, which is the main conductivity channel, degrades the electrical properties; however, it increases the hardness, thereby improving the overall physical properties.…”
Section: Resultsmentioning
confidence: 99%
“…however, a portion of the ceramic particles retained their shapes and were not alloyed. This indicated that sintering of the green compact, produced after pressing the mixed powder, may create voids owing to the ceramic particles that were deformed or retained their shape, resulting in the formation of pores in the composite [10][11][12][13]. The uniform distribution of additives in the Cu base, which is the main conductivity channel, degrades the electrical properties; however, it increases the hardness, thereby improving the overall physical properties.…”
Section: Resultsmentioning
confidence: 99%